An Introduction to Sobolev Spaces and Interpolation Spaces - Tartar, Luc (Lecture Notes of the Unione Matematica Italiana, 2007)
After publishing an introduction to the Navier-Stokes equation and oceanography (Vol. 1 of this series), Luc Tartar follows with another set of lecture notes based on a graduate course in two parts, as indicated by the title. A draft has been available on the internet for a few years. The author has now revised and polished it into a text accessible to a larger audience.